A calf index for monitoring reproductive success in the BeringChukchi-Beaufort Seas bowhead whale (Balaena mysticetus) population - Koski , W. R.; Zeh, J.; George , J. C. (J. Cetacean Res. Manage., 2023)
The percentage of calves in a whale population can provide information on whether a population is increasing, stable or decreasing and is an input to population models. In this paper a method for estimating the percentage of calves in the Bering-Chukchi-Beaufort Seas (B-CB) bowhead whale population in any given year by obtaining information on the percentage of calves passing Point Barrow, Alaska, during the last three weeks of the spring migration is presented. The method incorporates information on the timing of the migration with the percentage of calves detected during calf index surveys conducted during weekly periods from 14 May to early June. Historic data provide the different proportions of the migration during the weekly periods during low, medium and high calf years. The index is adjusted to allow for calves passing before 14 May and calves that are born after their mothers pass Point Barrow. The calf index was calculated for eight years using data from aerial photographic surveys near Point Barrow from 1985 to 2004 and the mean percentage of calves in the sampled years was 6.1%. Power analyses indicate that nine years of calf index data are required following a decline to detect a 60% reduction in the calf index. Additional calf index surveys prior to a decline would increase the power to detect a decline. This method can provide a robust estimate of the percentage of calves in the population each year with a modest aerial survey or photographic effort at Point Barrow. The data would be valuable in evaluating whether calving rates are within the range tested for the purpose of reviewing the B-C-B bowhead whale Strike Limit Algorithm.